Interkonfessionalität und Irenik: Gesprächsstile zwischen Protestanten und Katholiken von 1555 bis 1800 - Spehr, Christopher (Catholica <Münster>, 2022)
The essay is dedicated to the different attempts of Protestants and Catholics to overcome confessional differences since the Peace of Augsburg in 1555. On the basis of four examples, the styles of conversation used by princes, theologians, politicians or private individuals to reach an understanding are examined. They range from the Worms Religious Conversation of 1557 to the Thorner Religious Conversation of 1645 and Rojas' Reunion Conversations to interconfessional private conversations in the Enlightenment period. Although all attempts ultimately failed, in the long term they prepared the ground on which Catholic-Protestant ecumenism could build in the 20th century.